Analysis of Spatial Patterns of Settlement, Internal Migration, and Welfare Inequality in Zimbabwe - Swinkels, Rob (World Bank, Washington, DC, 2019)
This report aims to assess the spatial dimensions of settlement, internal migration, and welfare inequality in Zimbabwe, explore their relationship and implications, and identify policy options for addressing spatial disparities in social outcomes. It is exploratory in nature and identifies areas for further research to continue to unravel the drivers of the pattern that is observed. The study looks at where people are today (chapter 2), unpacks urbanization trends, and reviews population density and connectivity (chapter 3). Chapter 4 assesses the reasons behind the spatial settlement patterns and looks at Zimbabwe’s historical land allocation, land reform, and economic crisis in the 2000s. Chapter 5 discusses the consequences of this spatial distribution of the population in terms of poverty, nonfarm employment, and service delivery outcomes. Chapter 6 discusses policy implications.